2010
DOI: 10.1111/j.1750-3841.2010.01831.x
|View full text |Cite
|
Sign up to set email alerts
|

Aroma Profile and Volatiles Odor Activity Along Gold Cultivar Pineapple Flesh

Abstract: Physicochemical attributes, aroma profile, and odor contribution of pineapple flesh were studied for the top, middle, and bottom cross‐sections cut along the central axis of Gold cultivar pineapple. Relationships between volatile and nonvolatile compounds were also studied. Aroma profile constituents were determined by headspace solid‐phase microextraction at 30 °C, followed by gas chromatography/mass spectrometry analysis. A total of 20 volatile compounds were identified and quantified. Among them, esters wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 22 publications
2
39
0
Order By: Relevance
“…Hexanal has often been detected during SPME analyses of grapes (Sánchez-Palomo, Díaz-Maroto, & Pérez-Coello, 2005) and other fruit (Eugenio et al, 2010;Osorio et al, 2011;Porto, Decorti, & Tubaro, 2010), increasing the intensity of aroma (Fraternale, Ricci, Flamini, & Giomaro, 2011;Montero-Calderón, Rojas-Graü, & Martín-Belloso, 2010). Hexanal was associated with these fruits through the common enzyme lipoxygenase that converts linoleic acid and a-linolenic acid (Feudo et al, 2011).…”
Section: Ketones and Aldehydesmentioning
confidence: 97%
See 2 more Smart Citations
“…Hexanal has often been detected during SPME analyses of grapes (Sánchez-Palomo, Díaz-Maroto, & Pérez-Coello, 2005) and other fruit (Eugenio et al, 2010;Osorio et al, 2011;Porto, Decorti, & Tubaro, 2010), increasing the intensity of aroma (Fraternale, Ricci, Flamini, & Giomaro, 2011;Montero-Calderón, Rojas-Graü, & Martín-Belloso, 2010). Hexanal was associated with these fruits through the common enzyme lipoxygenase that converts linoleic acid and a-linolenic acid (Feudo et al, 2011).…”
Section: Ketones and Aldehydesmentioning
confidence: 97%
“…The same phenol thermal degradation products were found in thermally processed pomegranate juice . One of the phenols from pomegranate juice, 4-ethyl-2-methoxy phenol, was also found in pineapple aroma, perhaps indicating that this particular phenol was an oxidation product rather than being thermally produced (Montero-Calderón et al, 2010).…”
Section: Phenolsmentioning
confidence: 98%
See 1 more Smart Citation
“…Volatiles have been determined by gas chromatography-mass spectrometry (GC-MS) to reveal the aroma differences among sweet osmanthus cultivar groups, but different extraction methods might affect volatile composition (Zhu et al, 1985;Wang et al, 2009;Hu et al, 2012). Solid-phase microextraction (SPME), a simple, rapid, sensitive, and solvent-free technique for flower aroma analysis, is considered largely to retain the natural aroma (Montero-Calderón et al, 2010). Using SPME, Xin et al (2013) found a high degree of similarity in aroma characteristics within the same cultivar group, and that the high relative contents of cis-and trans-linalool oxide (furan), trans-2-hexenal, and cis-3-hexen-1-ol might affect the aromas of sweet osmanthus.…”
Section: Introductionmentioning
confidence: 99%
“…Fruits in general contain volatile compounds as described by Pino et al (7), Monteiro-Calderón et al (8) and Licciardello et al (9). The volatile chemicals present in natural leaves, flowers and fruits have been widely used in aromatherapy since ancient times, suggesting that they impart some beneficial health effect in addition to their pleasant odor.…”
Section: Introductionmentioning
confidence: 93%